Modern predators : the science, sovereignty, and sentiment of wildlife conservation in Zambia. - Godfrey, Elizabeth (My University, 2014)
This dissertation presents the suspicions and tensions encountered during ethnographic fieldwork with (what I call) the Predator Project Zambezi (PPZ), a WWF-funded research and conservation organization based in Zambia. It extrapolates the broader contexts of this uneasiness and situates it within global conservation discourses. The distrust that manifests between the wildlife authorities in Zambia, the residents of rural areas, and PPZ epitomizes postcolonial contentions over state sovereignty and the continued hegemony of Euro-American environmental ideologies. Moreover, the objective perspective that is claimed by PPZ as a scientific organization is challenged through analysis of its daily epistemic contradictions. In this ethnography, I show how the priorities of conservation institutions as communicated through PPZ ultimately work to arrest the post-colonies in a continuous state of catching up to the eco-modern condition that is ascribed to the global North.
Keywords: Wildlife conservation - Zambia.